Retrospective Evaluation of the Clinical Findings and Bone Mineral Densitometry Results of Children with Celiac Disease - Sezin Naiboğlu (Bagcilar Medical Bulletin, 2020)

(untitled)
Objective:Children diagnosed with Celiac disease should be closely followed-up for osteoporosis that may develop. We aimed to evaluate the osteoporosis conditions through bone densitometry in patients with the diagnosis of celiac disease, who were given a strict gluten-free diet.Method:The complaints at the time of admission, anthropometric data, laboratory findings at the time of admission, laboratory findings after gluten-free diet and bone densitometer results of 80 patients, who were followed-up at the pediatric gastroenterology outpatient clinic of our hospital and diagnosed with Celiac disease, were retrospectively investigated.Results:The study was conducted between December 2015 and February 2016 with patients diagnosed with Celiac disease. The study was conducted with a total of 80 cases, 31 (38.8%) boys and 49 (61.3%) girls. The mean age of the cases was 10.01±4.75 years. While the most common symptoms of the cases with gastrointestinal system findings were abdominal pain and diarrhea, the most common findings apart from the gastrointestinal system were growth and developmental delay and anemia. In our study, the frequency of osteoporosis was 14%.Conclusion:In our study, it is shown that the majority of children diagnosed with Celiac disease apply to the hospital with findings apart from the gastrointestinal system or asymptomatically. It is important to carefully question the non-gastrointestinal system findings of the disease. Requesting Bone Mineral Densitometry in the follow-up of Celiac disease is an important marker for diagnosis and increase in length of patients with osteoporosis.